Transitional Care Models for Stroke Survivors to Improve Quality of Care through Bridging the Care Gap from Hospital to Home: A State of Art Review - Paudel, Kalpana; Banstola, Ratna Shila (Journal of Nursing Education of Nepal, 2022)
Introduction : Stroke is a life threatening medical emergency that occurs suddenly and impact greatly in all aspect of an individual’s normal life since the early stage to long term. Various types of transitional care models are using by Health systems to improve care transition among stroke patients. Aims:This paper aims to explore the existing transitional care models used to improve the quality of care and patient’s outcome among stroke survivors.Methods: An Integrated review was conducted of empirical literature available in PubMed, Google Scholar, ProQuest, and NepJol by June 20, 2022 to identify studies of hospital to home care transitions of stroke patients with quality of care as the primary outcome.Results: There are 6 main types of transitional care model which focused on care transition for stroke survivors: 1) Naylor’s Transitional Care Model (TCM), 2) Coleman’s Care Transition Interventions (CTI), 3) Project Re-engineered Discharge (project RED), 4) Better Outcomes by Optimizing Safe Transition (Project Boost), 5) Enhanced Discharge Planning Program and 6) Comprehensive Post- Acute Stroke Services (COMPASS). Although, all models are differing by design, each of the models can provide a framework for managing health conditions from hospital to home settings in collaboration with the client and his/her family. Hence, the transitional care Models are effective in bridging the care gap between hospital to home and improve the quality of health care and patient outcomes among stroke survivors.
Keywords: Strokes; Transitional care; Care transition; Transitional care model; Early discharge planning